2016
DOI: 10.1371/journal.pone.0164820
|View full text |Cite
|
Sign up to set email alerts
|

Variation Analysis of Physiological Traits in Betula platyphylla Overexpressing TaLEA-ThbZIP Gene under Salt Stress

Abstract: The aim of this study was to determine whether transgenic birch (Betula platyphylla) ectopic overexpressing a late embryogenesis abundant (LEA) gene and a basic leucine zipper (bZIP) gene from the salt-tolerant genus Tamarix (salt cedar) show increased tolerance to salt (NaCl) stress. Co-transfer of TaLEA and ThbZIP in birch under the control of two independent CaMV 35S promoters significantly enhanced salt stress. PCR and northern blot analyses indicated that the two genes were ectopically overexpressed in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Increasing the number of primers, however, improved the ability to distinguish genetic differences between different provenances. With 15 pairs of SRAP primers, the percentage of detectable polymorphic loci was above 98.5% [55] . Of 583 B. platyphylla trees, 100 were selected after measuring the length of individual fibers.…”
Section: Development Of Molecular Markers and Construction Of Geneticmentioning
confidence: 89%
See 1 more Smart Citation
“…Increasing the number of primers, however, improved the ability to distinguish genetic differences between different provenances. With 15 pairs of SRAP primers, the percentage of detectable polymorphic loci was above 98.5% [55] . Of 583 B. platyphylla trees, 100 were selected after measuring the length of individual fibers.…”
Section: Development Of Molecular Markers and Construction Of Geneticmentioning
confidence: 89%
“…The heterogenous Tamarix TaLEA-ThbZIP gene was transferred into B. platyphylla and nine transgenic lines showing drought resistance and salt tolerance were obtained, including five transgenic lines containing LEA genes which could grow normally in soil containing 0.5% NaCl and four transgenic lines expressing bZIP genes. The results indicated that these transgenic lines had improved drought resistance and salt tolerance [55] .…”
Section: Transgenic Betula Platyphyllamentioning
confidence: 93%
“…Abiotic stress tolerance is a complex quantitative trait, and significant differences have been observed in stress resistance among species, or even genotypes of the same species [ 32 , 33 , 34 ]. Survival rates of five U. pumila cultivars pointed to significantly different levels of salt tolerance, implying that these cultivars might be suitable for afforestation of soils with different salinity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll fluorescence images were obtained using the Chlorophyll Fluorescence System (Heinz-Walz Instruments, Effeltrich, Germany) according to the manufacturer's instructions. Malondialdehyde (MDA), peroxidase (POD), superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) activities were measured by absorption photometry using a spectrophotometer, according to the method described by Song et al [61,62].…”
Section: Measurement Of Chlorophyll Fluorescence Physiological and mentioning
confidence: 99%